El Salvador : Technical Assistance Report-Balance of Payments, International Investment Position, and Secondary Income Statistics (July 14-22, 2014). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission regarding the balance of payments, international investment position, and secondary income statistics in El Salvador. The mission reviewed progress made on the recommendations for the Coordinated Direct Investment Survey (CDIS). Although El Salvador is currently reporting data to the CDIS, there are some topics that need improvement, particularly the positions of the shareholders of the three most important financial groups and their subsidiaries to avoid duplicate entries. The mission agreed with the authorities regarding the monitoring of processing payment vouchers sent to the Central Reserve Bank of El Salvador by banks and other entities paying remittances for amounts exceeding the threshold of USD 500 to complete the personal transfers' estimates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet